Public Willingness to Pay For Purple Corn Attributes - Norzalila Kasron; Nurul Nadia Ramli; Rawaida Rusli; Nur Fazliana Md. Noh; Nor Azlina Saari (Universitas Ahmad Dahlan, 2023)
Sweet corn (Zea mays L. saccharata), also known as sugar corn or sweet maize, is a popular multi-purpose cereal crop of the family Poaceae (Muhumed et al., 2014). The crop is the second most important crop in Asia after rice. China remains as the largest producer with a production of 260 million MT in 2019. In Malaysia, the crop area is estimated 10 thousand ha with production yield of 73 thousand MT. Purple variety that rich with anthocyanin content is classified as sweet corn that relatively new in local market. The cultivation of purple corn is not encouraging as Malaysian Department of Agriculture (DOA) recorded only eight farmers throughout Malaysia with a total area of 17.7 ha. Considering this variety is new and less accessible, this study evaluates consumers’ Willingness to Pay (WTP) in Malaysia towards purple corn. Data was collected through online platforms using structured questionnaires. The total of 431 responses were received in one month. The discrete choice experiment (DCE) is used to measure consumer WTP and the results showed that anthocyanin content and sweetness of purple corn are positive and significant at the level of 1%. This indicated that the higher the anthocyanin content and corn sweetness, the higher the level of consumer utility would be. Consumers are willing to pay for higher prices than the lowest market price if the purple corn variety satisfies both value-added anthocyanin and sweetness attributes.